Analisis Kesetabilan Lereng Studi Kasus Area Tambang Rakyat di Bukit Tui S0°28'43.15" E100°24'16.24"-S0°28'43.15" E100°24'15.28" Kecamatan Padang Panjang Barat Kabupaten Padang Panjang - Helky Sandra; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Tui Hill is a limestone hill lined south of Padang Panjang, located between Rao-Rao Village to Tanah Hitam. The results of research at Tui Hill at the location S0 ° 28'43.15 "E100 ° 24'16.24" - S0 ° 28'43.15 "E 100 ° 24'15.28" located in Tanah Hitam Village has a covered dolomite rock slope. Based on the situation that occurs there are several factors that can relate to avalanches. such as rainfall, steep slope geometry, high excavation and earthquake vibration. The potential for landslides on the research slopes could endanger dolomite miners in the slope location. In addition, material due to landslides can cause road closures to obstruct road user traffic. This study aims to analyze and make treatment recommendations so that slope conditions become safe / stable. Safe slope analysis is based on the value of the safety factor (FK), namely Bowles, that (FK) so that the stable slope is FK> 1.25. Based on the results of the analysis and calculations it was found that the value of the slope safety factor (FK) on the A-A 'section is 2,631 and the B-B' section is 2,342. Based on the results of the analysis, it was found that the value of the slope safety factor (FK) in the A-A 'is 2,200 and B-B' section is 1,943.Keywords: Slope Stability Analysis, Safety Factor, Earthquake Vibration, Plane Failure, Slope Soil